Kontribusi Praktek Kerja Industri Dan Kemampuan Akademis Terhadap Persepsi Siswa Tentang Kesiapan Memasuki Dunia Kerja - Muspawi, Mohamad; Pratama, Robin; Sarlles, Monika (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2020)
This study aims to analyze the contribution of industrial work practice and academic ability towards students' perceptions of readiness to enter the world of work in class III of the Office Administration Department of SMKN 1 Jambi. This study used a quantitative method with a sample size of 84 respondents. The research data were obtained by distributing questionnaires to students, then were analyzed by inferential statistics using simple regression and multiple regression data analysis techniques. Based on the results of the study, it was known that the contribution of X1 to Y was 22.7% with the regression equation Y = 50.962 + 0.942 X, which means that there was a positive effect of X1 on Y. Furthermore, the contribution of X2 to Y was 32.8% with the regression equation Y = 46.074 + 0.867 X, which means that X2 had a positive effect on Y. Then, the contribution of X1 and X2 to Y was 42.4% with the regression equation Y = 29.026 + 0.691 X1 + 0.727 X2. This means that the effect of industrial work practices (X1) and academic ability (X2) together (simultaneously) on readiness to enter the world of work (Y) was 42.4%, the remaining 57.6% was influenced by other factors. Thus, it can be concluded that industrial work practices and academic abilities contribute to students' perceptions of readiness to enter the world of work.